The Influence of Store Atmosphere, Service Quality, Product Quality, and Price on Customer Satisfaction - Munawaroh, Madaniah; Simon, Zainal Zawir (SAN Scientific, 2023)
This research was conducted with the aim of examining the effect of Store Atmosphere, Service Quality, Product Quality and Price on Customer Satisfaction on One Pintu Coffee Customers in Bandung. This research uses explanatory research. The population of this research is customers who are or have used One Door services and products with a total of 100 respondents. Data was collected using a survey method with a questionnaire instrument. Data analysis using multiple linear regression analysis. The results of the study show that: (1) Store atmosphere has a positive and significant effect on customer satisfaction. (2) Service Quality has a positive and significant effect on Customer Satisfaction. (3) Product Quality has a positive and significant effect on Customer Satisfaction. (4) Price has a positive and significant effect on customer satisfaction. (5) Simultaneously Store Atmosphere, Service Quality, Product Quality and Price have a significant effect on Customer Satisfaction at One Pintu Coffee.